Comprometimento com o trabalho de policiais militares do Programa Ronda do Quarteirão do Ceará - Dourado, Larissa Façanha de Mattos (2014)
The present work is an analysis of the dimensions of the construct "commitment at work" in the context of military professional officers linked to the Ceará City Block Patrol Program. The identification of the related psychological dimensions was determined according to the perception of these military professional officers’ practices by the application of a scale and by the conduction of a focus group. The main objective was to characterize the work commitment from the perception of the police themselves, in order to analyze their relationship with their professional practice in parallel to a questioning of the proposed model of community policing “Ronda do Quarteirão – City Block Patrol”. The survey sample focused on the City Block Patrol members who volunteered to answer the scale and to take part in a focus group, which aimed to improve the comprehension of the variables related to the core category of the study. It was also applied a six dimension scale, that differentiates the type of commitment in six psychological dimensions as proposed by Rego in a digital version in Google Forms, The data were treated by simple descriptive statistics though the SPSS software, while the data collected in the focus group were transcribed and interpreted and liked to those collected by the quantitative approach. Based on the quantitative results, we found low levels in all dimensions of commitment concerning the applied scale. Qualitative data confirmed that information regarding the low job satisfaction indicated by professional. There is though a gap between the professional practices and the proposed model of community model of intervention by the police, which has its origins in other cultures. It is possible to conclude that the context of the work of the City Block Patrol has negative traits that can prevent an improvement of the affective nature of commitment, by presenting a wide gap between the goal and philosophy of City Block Patrol Model and their actual practices. They feel themselves criticized by reference members of the Program as well as threatened by them, what can discourages them in a curate and previously intended working practice. The research findings could also contribute to increase the conceptual appliance of Psychology within the investigated field and open the possibility for future studies focusing intervention and reflection on police training and psychological health issues in this occupational expanding category.